Endometriosis-associated Maternal Pregnancy Complications – Case Report and Literature Review - Petresin, J.; Wolf, J.; Emir, S.; Müller, A.; Boosz, A. S. (Geburtshilfe und Frauenheilkunde, 2016)
The incidence of endometriosis is increasing. Particularly during pregnancy and labour, clinicians should be alert to possible endometriosis-associated complications or complications of previous endometriosis treatment, despite a low relative risk. In addition to an increased rate of early miscarriage, complications such as spontaneous bowel perforation, rupture of ovarian cysts, uterine rupture and intraabdominal bleeding from decidualised endometriosis lesions or previous surgery are described in the literature. Unfavourable neonatal outcomes have also been discussed. We report on an irreducible ovarian torsion in the 16th week of pregnancy following extensive endometriosis surgery, and an intraabdominal haemorrhage due to endometriosis of the bowel in the 29th week of pregnancy.
Keywords: endometriosis; pregnancy; complication; delivery; decidualization; intraabdominal bleeding